Effect of different black-out materials on off-season pot mum production of chrysanthemum (Dendranthema grandiflora) - DHIMAN, S R; GUPTA, Y C; THAKUR, PRIYANKA; KASHYAP, BHARATI; SHARMA, MEENAKSHI; SHARMA, KHUSHBOO (The Indian Journal of Agricultural Sciences, 2018)
The present investigation on effect of different black-out material(s) on off-season pot mum production of chrysanthemum (Dendranthema grandiflora Tzevelev) was carried out at the experimental farm of the Department of Floriculture and Landscape Architecture, Dr Y S Parmar University of Horticulture and Forestry, Nauni, Solan (H.P.) during 2011. The investigations were conducted on 10 selections/cultivar of chrysanthemum. Off-season flowering was induced by providing artificial short days (16 hr dark period with effect from 5.00 pm to 9.00 am) starting from 9 June 2011, till 60-70% flower buds showed colour. Artificial short days were provided by three different materials, viz. Tarpaulin, High density polyethylene – White outside and black inside, Black satin cloth. Findings revealed that among different covering materials, HDPE resulted in minimum days for visible flower bud formation in ‘UHFSChr -43’ (60.67) and maximum diameter of flower in ‘UHFSChr -68’ (4.22 cm). However, black satin cloth recorded maximum plant height in cultivar ‘Ajay’ (70.00 cm), number of flowers per pot and number of flowers per plant in ‘UHFSChr -64’ (367.30 and 123.00 respectively). In this experiment, all selections/cultivar tried for off –season pot mum production under different black out materials flowered successfully. Among different black-out materials used, HDPE was best for Solan –Nauni conditions of Himachal Pradesh.